Attitude and beliefs in students of Bellvitge Campus on hygienic rules and standard caution - Carmen López Matheu; Enrique Limón Cáceres; Isabel Oto Clavero; Jordi Carratala Fernández; José Enrique Espasa Suárez de Desa; Vicente Lozano de Luaces; Baldiri Prats Climent; José María Ramón Torrell (Universidad de Alicante, 2012)
In the latest years some new and important advances in fields of self-protection facing infections had been produced. In the teaching side, those who teach theory related to self-protection in health and hygiene personnel within the different Health and Science Courses in the Bellvitge Campus (CB) in the University of Barcelona (UB), an important lack of knowledge and confusion was detected in subjects related to patient and professional security. Aims: To enhance education and knowledge in Health Sciences of CB in the BU regarding basic hygienic means. Material & Method: A study of field was advised: causes and comparatively. A group of teachers implied in the subjects gathered together in order to determine and deepen in the syllabuses to establish common criteria to fulfil a real analysis of present the situation. Semi-structured interviews to two students within the different courses were done, registered and transcribed literally for a further analysis (Atlas/Ti19). Results and Discussions: From the discourse four categories were established: 1) Learning: Students underline lack of agreement among teachers and an extreme theoretical teaching. 2) Work experience: Students underline opposition in theory and practice. 3) Personal considerations: Students link measures with exceptional situations (extremely invasive techniques). The speech of do not hurt the patient is always present. 4) Peculiarities inherent to each different university courses: Students perceptions are completely different according to their very different education programmes. Conclusions: Preventing and hygienic measures matters within the different university programmes are considered in the study programmes punctually but not continuously. Students perceive them as a necessary education due to their lack of experience but no more than acquiring certain skilfulness. Regarding Health Centres and Hospitals there is not a mutual agreement in whether professionals should take into consideration as compulsory those preventing and hygienic measures in daily practice, and even theory and practice criteria deeply differ in such instances.